Hukum Pengambilan Untung Dari Dana Wakaf di Lembaga Bantuan Sosial (Studi Kasus di Yayasan Human Initiative) - Xavier Halim; Akhmad Husaini (ITB AAS INDONESIA Surakarta, 2023)
Waqf cash which is collected and managed by the Human Initiative foundation, places more emphasis on cluster empowerment to improve the quality of life of the beneficiaries of the program called the Initiative for Empowerment and facilitates the community through empowerment and using all the potential the foundation has to overcome their problems. The research conducted by obtaining data goes directly to the field or field research. Meanwhile, the information is used in a qualitative approach when viewed from the data. In Law No. 41 of 2004, the net return from the management and development of waqf assets is approximately 10%. However, the programs raised by the Human Initiative are waqf programs whose benefits are received directly by mauquf 'alaih. This is different from the notion of productive waqf described previously. In essence, the characteristics of the waqf program in the Human Initiative are direct waqf because of the collection of funds from the public for the designation of waqf whose objects are not movable. Then the Human Initiative does not receive returns on the management of waqf assets or zero (0%) because the waqf managed by the Human Initiative is an immovable property waqf or consumptive waqf whose benefits are directly felt by the community/social virtues.